Determination of optimum Al content in HA‐Al2O3 nanocomposites coatings prepared by electrophoretic deposition on titanium substrate. Issue 4 (20th November 2017) - Askari, Nayereh; Yousefpour, Mardali; Rajabi, Masoud
Abstract: In this research work, Hydroxyapatite (HA)‐Al2 O3 bio nanocomposite coatings were coated on titanium substrate by electrophoretic deposition (EPD) and reaction bonding process. The reaction bonding process densifies the coating and creates small uniform porosities. HA‐Al2 O3 bio nanocomposite coatings were analyzed by X‐ray diffraction (XRD) and field emission scanning electron microscopy (FE‐SEM). For the coatings sintered for 2 hours at 850°C, XRD results demonstrated no significant HA decomposition. The adhesion strength increased from 10.2 MPa to 25 MPa. It was determined that 50 wt.% of Al is the optimum content for producing free‐of‐crack composite coatings on the titanium surface as shown by SEM examination.